(untitled) (Journal of Contemporary Issues in Accounting, 2026)
This study investigated board’s diversity on tax aggressiveness of the listed non-financial firms. Adopting the expo-facto research design using secondary data, a total of 70 firms out of 109 firms in the non-financial sectors listed on the Nigerian Exchange Group as at December 2010 were purposively sampled based on their consistent, uninterrupted operations during the period. Data extracts from the audited financial reports of the firms and the Nigerian Exchange Group factbook for the periods 2011 to 2021 were analyzed using standard deviation, percentages, regression analysis (panel fixed effect and random effect model). The results revealed that board diversity, proxied by ethnic background diversity, had significant negative effect on corporate tax aggressiveness (t = -2.88; p<0.05), even as board gender diversity (t = -3.27; p<0.05) and board independence (t = -4.93; p<0.05) negatively affected corporate tax aggressiveness significantly.